Descrição do plexo braquial do cachorro-do-mato (Cerdocyon thous Linnaeus, 1766) - Pinheiro, Luane Lopes; Branco, Érika; Souza, Damazio Campos [UNESP]; Pereira, Luiza Helena Corrêa; Lima, Ana Rita (Universidade Federal de Goiás, 2014)
The Cerdocyon thous is a canid that has a wide distribution in South America and, besides some general aspects, its morphology is little known in the literature, especially regarding the nervous system. With the aim of elucidating the anatomical composition of brachial plexus, we studied three male specimens from Paragominas-PA, donated to the Morphological Laboratory of Animal Research (LaPMA), Federal Rural University of Amazonia (UFRA), after death by trampling. The animals were fixed in an aqueous solution of 10% formaldehyde for bilateral dissection of the origin of the brachial plexus. The brachial plexus of C. thous is derived from the last three cervical nerves and the first thoracic nerve (C6-T1). The main nerves that compose it, with their respective origins were the suprascapular nerve, subscapular nerve and musculocutaneous nerve (C6-C7), axillary nerve (C7-C8), radial nerve (C7-T1 and C7-C8), median nerve, ulnar nerve, thoracodorsal and thoracic lateral nerve (C8-T1). We conclude that the brachial plexus of C. thous is similar to that described for the domestic dogs, showing small differences in the composition of some nerves.

O Cerdocyon thous é um canídeo que possui ampla distribuição na América do Sul e, salvo aspectos gerais, têm sua morfologia pouco conhecida na literatura, principalmente no que tange ao sistema nervoso. Com o objetivo de elucidar a composição anatômica do plexo braquial, estudaram-se três exemplares machos provenientes de Paragominas-PA, doados após morte por atropelamento ao Laboratório de Pesquisa Morfológica Animal (LaPMA), da Universidade Federal Rural da Amazônia (UFRA). Os animais foram fixados em solução aquosa de formol 10% para posterior realização da dissecação bilateral da origem do plexo braquial. O plexo braquial do C. thous é derivado dos três últimos nervos espinhais cervicais e do primeiro nervo torácico (C6-T1). Os principais nervos que o compõem, com suas respectivas origens foram: n. supraescapular, n. subscapular e n. musculocutâneo (C6-C7), n. axilar (C7-C8), n. radial (C7-T1 e C7-C8), n. mediano, n. ulnar, n. toracodorsal e n. torácico lateral (C8-T1). Concluímos que o plexo braquial do C. thous assemelha-se ao descrito para os cães domésticos, apresentando pequenas diferenças quanto à composição de alguns nervos.
Description of plexus brachial of crab-eating foxes (Cerdocyon thous Linnaeus, 1766)
Keywords: anatomia; Cerdocyon thous; plexo braquial; anatomy; brachial plexus; Cerdocyon thous